2017
DOI: 10.1158/1535-7163.mct-16-0314
|View full text |Cite
|
Sign up to set email alerts
|

A Fas Ligand (FasL)-Fused Humanized Antibody Against Tumor-Associated Glycoprotein 72 Selectively Exhibits the Cytotoxic Effect Against Oral Cancer Cells with a Low FasL/Fas Ratio

Abstract: Altered expression of the Fas ligand (FasL)/Fas ratio exhibits a direct impact on the prognosis of cancer patients, and its impairment in cancer cells may lead to apoptosis resistance. Thus, the development of effective therapies targeting the FasL/Fas system may play an important role in the flght against cancer. In this study, we evaluated whether a fusion protein (hcc49scFv-FasL) comprising of the cytotoxicity domain of the FasL fused to a humanized antibody (CC49) against tumor-associated glycoprotein 72, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…NA cell line was established as a fibronectin-producing cell line (14). Furthermore, it has been reported that the cytotoxicity of anti-cancer reagents in OSCC has been evaluated in SQUU-A cell line and SQUU-B cell line (15), SAS cell line (16), NA cell line (17) using various conventional methods. That is why, we selected four these cell lines with each characteristic feature in the present study, which were also used in cytotoxic assay in previous study.…”
Section: Introductionmentioning
confidence: 99%
“…NA cell line was established as a fibronectin-producing cell line (14). Furthermore, it has been reported that the cytotoxicity of anti-cancer reagents in OSCC has been evaluated in SQUU-A cell line and SQUU-B cell line (15), SAS cell line (16), NA cell line (17) using various conventional methods. That is why, we selected four these cell lines with each characteristic feature in the present study, which were also used in cytotoxic assay in previous study.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific activity of the hFasLECD sample was at least 20 times higher than an anti-mouse FasR agonistic monoclonal antibody, Jo2, in inducing apoptosis against FasR overexpressing mouse cells, and showed much less toxicity with regard to the liver failure in vivo [ 5 ]. To overcome the above mentioned problem, numerous studies for delivering the protein specifically toward the target cells have been made by exploiting the gene-fusion technology using the genes of single chain variable fragments of the cell-surface antigen recognizing antibodies and the extracellular domains of cytokines as the fusion components [ 6 10 ]. On the other hand, the administration of many cytotoxic drugs, including the ones in clinical uses, is known to significantly affect the number of cell-surface hFasR, which determines the susceptibility to apoptosis execution by hFasL [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial translational potential for our understanding of the roles and regulation of various forms of released Fas ligand. This includes development of novel approaches to treatment with, for example, FasL-fused humanized antibodies to sensitize target cells to cell death [ 108 , 109 , 110 ] as suggested in glaucoma treatment [ 111 , 112 ], novel forms of RNA therapy [ 113 ], prognosis of long-term allergic outcomes at birth [ 114 ] or even for schizophrenia treatment [ 115 ]. However, there remain a number of outstanding problems that need to be addressed with regard to soluble Fas ligand as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%